AGB carbon stock analysis in the Indigenous agroforestry of the Ecuadorian Amazon: Chakra and Aja as Natural Climate Solutions - Álava-Núñez, Paulina; Torres, Bolier; Castro, Miguel; Robles, Marco (Frontiers in Forests and Global Change, 2025)
Natural Climate Solutions (NCS) aim to enhance carbon sequestration by restoring and managing various ecosystems while ensuring environmental and socio-economic stability. They also focus on identifying and implementing management actions with the highest mitigation potential. In the Ecuadorian Amazon, Indigenous communities have traditionally practiced a unique form of agriculture that integrates remnant trees within cultivated areas, known as Chakras or Ajas. These areas provide essential resources such as food, medicine, and other products. Despite the persistence of these practices, there has been a shift toward more market-oriented systems. The mitigation capacity of Chakras and Ajas is under-researched, leaving a gap in understanding their characteristics and potential to mitigate climate change. This study utilized inventory data to estimate the variability and range of carbon stocks in Chakras and Ajas at different stages and other typical land uses in the area. Data were collected through an extensive field survey comprising 171 measurement plots, 4.592 trees, 731 palms, and various crops. To represent the landscape heterogeneity of above-ground biomass (AGB) carbon stocks, plots were randomly located, representing a stratified sample of eight different land uses. This sampling was implemented with a 95% confidence interval and a 10% error margin. Additionally, two other land uses (primary forest and an expert-identified best agroforestry - Model Chakra) were included, although they were not statistically defined. The results indicate that on average, Chakras/Ajas have more AGB carbon than pastures and monocultures (25.5 vs. 4.38 MgCha−1). The best Chakras and Ajas can achieve a carbon mitigation potential comparable to secondary forests, with a maximum of 105.6 MgCha−1, further emphasizing the need to support these traditional practices. Additionally, these systems provide co-benefits such as enhanced biodiversity (Shannon index of 1.98 in Model Chakras), improved ecosystem structure, and valuable provisioning services. This study also highlights successful cases that can serve as models for implementing NCS strategies. Based on these findings, it is evident that Chakras and Ajas in the Ecuadorian Amazon possess significant carbon mitigation potential and provide essential resources, highlighting the importance of supporting these traditional agricultural practices as NCS over monocultures.